HIGHLY SIDEROPHILE ELEMENTS IN CHONDRITES - Horan M.F.; Walker R.J.; Morgan J.W.; Grossman J.N.; Rubin A.E. (My University, 2003)
The abundances of the highly siderophile elements (HSE), Re, Os, Ir, Ru, Pt and Pd, were determined by isotope dilution mass spectrometry for bulk samples of 13 carbonaceous chondrites, 13 ordinary chondrites and 9 enstatite chondrites. These data are coupled with corresponding 187Re-187Os isotopic data reported by Walker et al. [Geochim. Cosmochim. Acta, 2002] in order to constrain the nature and timing of chemical fractionation relating to these elements in the early solar system. The suite of chondrites examined displays considerable variations in absolute abundances of the HSE, and in the ratios of certain HSE. Absolute abundances of the HSE vary by nearly a factor of 80 among the chondrite groups, although most vary within a factor of only 2. Variations in concentration largely reflect heterogeneities in the sample aliquants. Different aliquants of the same chondrite may contain variable proportions of metal and/or refractory inclusions that are HSE-rich, and sulfides that are HSE-poor. The relatively low concentrations of the HSE in CI1 chondrites likely reflect dilution by the presence of volatile components.Carbonaceous chondrites have Re/Os ratios that are, on average, approximately 8% lower than ratios for ordinary and enstatite chondrites. This is also reflected in 187Os/188Os ratios that are approximately 3% lower for carbonaceous chondrites than for ordinary and enstatite chondrites. Given the similarly refractory natures of Re and Os, this fractionation may have occurred within a narrow range of high temperatures, during condensation of these elements from the solar nebula. Superimposed on this major fractionation are more modest movements of Re or Os that occurred within the last 0-2 Ga, as indicated by minor open-system behavior of the Re-Os isotope systematics of some chondrites.The relative abundances of other HSE can also be used to discriminate among the major classes of chondrites. For example, in comparison to the enstatite chondrites, carbonaceous and ordinary chondrites have distinctly lower ratios of Pd to the more refractory HSE (Re, Os, Ir, Ru and Pt). Differences are particularly well resolved for the EH chondrites that have Pd/Ir ratios that average more than 40% higher than for carbonaceous and ordinary chondrite classes. This fractionation probably occurred at lower temperatures, and may be associated with fractionation processes that also affected the major refractory lithophile elements. Combined, 187Os/188Os ratios and HSE ratios reflect unique early solar system processing of HSE for each major chondrite class.
Keywords: HIGHLY SIDEROPHILE ELEMENTS; CHONDRITES; ABUNDANCES